Meloidogyne microcephala n. sp. (Meloidogynidae), a Root-knot Nematode from Thailand - Cliff, Gean M. (Society of Nematologists, 1984)
Meloidogyne microcephala n. sp. is described and illustrated from specimens obtained from tobacco (Nicotiana tabacum L.) in Thailand. The female perineal pattern usually has a low dorsal arch, coarse striae, and a series of small cuticular flaps around the tail terminus. The stylet of the female is 14.4 μm long, with large, square to rectangular stylet knobs, The distinctive male head region is narrow, small, and truncate with a low, flattened head cap. The stylet length is 20.6 μm, and the knobs are small, angular, and set off from the shaft. Mean length of second-stage juveniles is 457.5 μm, and stylet length is 9.3 μm. The tail tip in the juveniles is set off from the rest of the tail as a small finger-like projection. M. microcephala reproduces by mitotic parthenogenesis, and has a chromosome number of 2n = 36.